BDNF is essential to promote persistence of long-term memory storage - Bekinschtein, Pedro Alejandro (2008)
Persistence is a characteristic attribute of long-term memories (LTMs). However, little is known about the molecular mechanisms that mediate this process. We recently showed that persistence of LTM requires a late protein synthesis- and BDNF-dependent phase in the hippocampus. Here, we show that intrahippocampal delivery of BDNF reverses the deficit in memory persistence caused by inhibition of hippocampal protein synthesis. Importantly, we demonstrate that BDNF induces memory persistence by itself, transforming a nonlasting LTM trace into a persistent one in an ERK-dependent manner. Thus, BDNF is not only necessary, but sufficient to induce a late postacquisition phase in the hippocampus essential for persistence of LTM storage.